Sullam al - Mustafidin: The Theological Discourse in Aceh in 17th Century - Rahmah, Nur (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
The 17th century was the era of glorious for the development of intellectual history in Aceh, which is characterized by the presence of four well-known scholars, one of them is Abdurrauf Singkel. His work entitled Sullam al - Mustafidin contains views on theology that comes from the teachings of the ahl Sunnah wa al - Jamaah which also confirmed its existence as a Sunni schoolar. Abdurrauf’s theological views has also become important notion in the middle of debate between Hamzah Fansuri and Nuruddin Arraniri about wujudiyah in Aceh in the 17th century. Although al - Mustafidin Sullam text does not explicitly answer the question of wujudiyah in Aceh, but most likely this text was written to neutralize the chaos of religious (read: wujudiyah) and calls on Muslims to return to I’tiqad ahl sunnah wa al -Jamaah.